Nefertiti's sun temple : a new cult complex at Tell el-Amarna - Williamson, Jacquelyn. (Harvard Egyptological Studies, 2016)
Nefertiti's Sun Temple publishes stone relief fragments excavated from the site of Kom el-Nana at Tell el-Amarna, Egypt, dating to approximately 1350 BCE. This is the first time relief fragments can be associated with a specific wall from a specific temple at Tell el-Amarna. Jacquelyn Williamson reconstructs the architecture, art, and inscriptions from the site to demonstrate Kom el-Nana is the location of Queen Nefertiti's 'Sunshade of Re' temple and another more enigmatic structure that served the funerary needs of the non-royal courtiers at the ancient city. The art and inscriptions provide new information about Queen Nefertiti and challenge assumptions about her role in Pharaoh Akhenaten's religious movement dedicated to the sun god Aten.